Effect of different irrigation and fertilizer coupling on the liquiritin contents of the licorice in Xinjiang arid area - Abudukeyoumu Abudurezike; Xinghong Liu; Gulimila Aikebaier; Ayixiamu Shawuer; Xiaoli Tian (Ecological Indicators, 2024)
The increasing worldwide demand for traditional herbs has been met by growing cultivated herbs. It is undoubtedly very important to seek a reasonable cultivation mode for the yield, quality and long-term production stability of traditional herbs. Glycyrrhiza is a commercial medicinal crop that is widely cultivated with high water and fertilizer application, in the arid areas of northwest China. Rational irrigation and fertilizer application are key factors for successful crop management. Studying water–fertilizer coupling effects in a drip irrigation system is critical for sustainable agricultural development in arid areas, such as that of Xinjiang in China, to find out the optimized water and fertilizer management. Therefore, a four-year field experiment was conducted to find out how the combination of four levels of irrigation quotas and four levels of fertilizer amounts would affect the different parts liquiritin contents of the licorice, data on different parts liquiritin contents of the licorice were collected from individual glycyrrhizin for each treatment during 2019 to 2022. The application of fertilizer significantly increased the liquiritin contents of the licorice under the same irrigation conditions. However, the liquiritin contents of the licorice were reduced in the excess water treatments (W4F1 and W4F4) and in the excess fertilizer treatments (W1F4 and W4F4) in contrast to the optimum W2F2 treatment. These results indicate that the combination of water and fertilizer management can potentially increase the accumulation the liquiritin contents of the licorice, which can be used to promote the cultivation of Glycyrrhiza.